Assessment of prevalence of dental caries and the associated factors among patients attending dental clinic in Debre Tabor general hospital: a hospital-based cross-sectional study - Yilkal Tafere; Selam Chanie; Tigabu Dessie; Haileyesus Gedamu (BMC, 2018)
Abstract Background Dental caries is the most common dental health problem caused by the interaction of bacteria on tooth enamel. Risk factors for dental caries include salivary composition and inadequate fluoride. However, other factors, such as standard of living, behavior, hygiene, eating habits, social status and socio-demographic factors, also contribute to the evolution of caries. Therefore, this study aimed to determine the prevalence of dental caries and associated factors among patients attending the dental clinic in Debre Tabor General Hospital in North West Ethiopia. Method An institution based cross-sectional study was conducted among 280 systematically selected patients attending Debre Tabor General Hospital dental clinic from May 8-20, 2017. The data were collected using pre-tested questionnaire and oral examination by a qualified dental professional. Basic hygienic procedures were observed during an oral examination. The teeth were examined for dental caries by the presence of decay, missing and filled teeth. The data were entered into Epi-Info version 3.5 and cleaned and analyzed using SPSS version 20. Descriptive summary of the data and logistic regression were used to identify possible predictors using odds ratio with 95% confidence interval and P-value of 0.05. Results A total of 280 subjects participated in the study; among whom 129 (46.1%) were female and nearly two-thirds of the respondents 208 (74.3%) attended formal education. The study revealed k8that the overall prevalence of dental caries was 78.2%. Dental caries was lower among respondents who had good oral hygiene status (AOR = 0.05, 95% CI, 0.02, 0.81). Dental caries was higher among participants who earned less than 5000 Eth Birr per month (AOR = 8.43, 95% CI, 2.6, 27.2). Dental caries was lower among respondents who had good knowledge (AOR = 0.51, 95% CI, 0.03, 0.64). Conclusions Prevalence of dental caries was high and found public health problem. Socioeconomic status, educational level, and poor oral hygiene practices were associated factors for dental caries. Health promotion about oral hygiene and integration of services are supremely important for the prevention of the problem of dental caries.